أهمية تبني التكنولوجيا المالية كآلية لتعزيز الشمول المالي -الإمارات العربية المتحدة نموذجا - بركان, عماد; حرنان, نجوى; عمان, أحمد (University of Eloued جامعة الوادي, 2022)
This study aims to shed light on the reality of financial technology within the United Arab Emirates, and how it contributes to enhancing the level of financial inclusion for it. The study reached a number of results, the most important of which are: The United Arab Emirates is witnessing a tremendous development in the use of financial technology, as this is embodied in the technologies that it has developed, and which have been applied in many fields. Good financial inclusion, and that the development of financial technology contributes significantly to enhancing its financial inclusion.
The Importance of Adopting FinTech as a Mechanism to Promote Financial Inclusion -The United Arab Emirates as a Model-
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: التكنولوجيا المالية، الشمول المالي، الإمارات العربية المتحدة; Fintech, Financial Inclusion, United Arab Emirates